2009
DOI: 10.1007/s00018-009-0220-2
|View full text |Cite
|
Sign up to set email alerts
|

Connexin32 hemichannels contribute to the apoptotic-to-necrotic transition during Fas-mediated hepatocyte cell death

Abstract: The present study was set up to investigate the fate of connexin32 and its channels in hepatocellular apoptosis. Primary hepatocyte cultures were exposed to Fas ligand and cycloheximide, and modifications in connexin32 expression and localization, and gap junction functionality were studied. We found that gap junction functionality rapidly declined upon progression of cell death, which was associated with a decay of the gap junctional connexin32 protein pool. Simultaneously, levels of newly synthesized connexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
0
41
0
2
Order By: Relevance
“…When BKtriggered oscillations were elicited in the presence of the general connexin channel blocker Cbx (25 M, 30-min preincubation and present during the 10-min observation window), the initial Ca 2ϩ spike remained, but the subsequent oscillations disappeared. We further applied two peptide connexin channel inhibitors, 32 Gap27 and 43 Gap26, that target Cx32 and Cx43 channels, respectively (36,48). Application of 32 Gap27/ 43 Gap26 ("Gap," 200 M, 30-min preincubation and present during the recording) also inhibited the Ca 2ϩ oscillations without perturbing the initial peak (Fig.…”
Section: Connexin Channel Blockers Inhibit Bk-induced Ca 2ϩ Oscillatimentioning
confidence: 99%
“…When BKtriggered oscillations were elicited in the presence of the general connexin channel blocker Cbx (25 M, 30-min preincubation and present during the 10-min observation window), the initial Ca 2ϩ spike remained, but the subsequent oscillations disappeared. We further applied two peptide connexin channel inhibitors, 32 Gap27 and 43 Gap26, that target Cx32 and Cx43 channels, respectively (36,48). Application of 32 Gap27/ 43 Gap26 ("Gap," 200 M, 30-min preincubation and present during the recording) also inhibited the Ca 2ϩ oscillations without perturbing the initial peak (Fig.…”
Section: Connexin Channel Blockers Inhibit Bk-induced Ca 2ϩ Oscillatimentioning
confidence: 99%
“…It has been suggested that these colocalised modifi cations in the expression of cytochrome P450 isoenzymes and Cx32 refl ect a defence mechanism to restrict the intercellular diffusion of reactive intermediates produced through xenobiotic biotransformation (Neveu et al, 1994). Furthermore, gap junctions, particularly those composed of Cx32, also act as goalkeepers of other aspects of the hepatocyte life cycle, including cell growth (Vinken et al, 2008) and apoptotic cell death (Vinken et al, 2010).…”
Section: Connexins and Liver Organogenesismentioning
confidence: 99%
“…Our group was the first to report the occurrence of Cx32 hemichannels in hepatocytes. Using an in vitro model of Fas-mediated apoptosis, a cell death mode involved in most liver pathologies, we found that de novo synthesized Cx32 gathers in hemichannels during apoptosis, and that hemichannel opening is critical for the termination of the cell death response [20] .…”
Section: Connexin Hemichannels In the Intestine And The Livermentioning
confidence: 99%